Do internship satisfaction and career aspiration influence Malaysia housemen self-perceived preparedness for independent hospital practice? - Abd. Manaf, Noor Hazilah; Adewale, Abideen Adeyemi; Borhan, Norfilzatun; Omar, Azura; Mohd, Dinon; Ismail, Izhairi; Abdul Hamid, Zabeda (2011)
The motivational and attitudinal dispositions of housemen perhaps suggest that numerous factors influence their career aspirations. Moreover, issues relating to the working and learning environment of housemen in the medical school is always topical. Obviously, these should have implication for their self-perceived preparedness for post-medical school practice. As such, this study investigates the relationship among internship satisfaction, career aspirations and perceived preparedness for medical practice among Malaysian housemen. A survey questionnaire was administered on all 2,046 housemen in all medical schools across Malaysia as at April 30, 2008 when data was collected. Data so obtained were subjected to statistical analysis based on N=1213 using both the structural equation modelling via SPSS AMOS 18 software. Although housemen reported significant issues relating to their satisfaction with learning and working environment, their response indicate a significant positive relationship between satisfaction and career aspiration. However, while satisfaction with the internship programme significantly influence their self-perceived preparedness for medical practice especially on some specific core skills, aspiration for medical career, though positive; was statistically insignificant.